Prognostic Impact of Preoperative Imaging Parameters on Resectability of Hilar Cholangiocarcinoma. (4th June 2013) - Ruys, Anthony T.; Busch, Olivier R.; Rauws, Erik A.; Gouma, Dirk J.; van Gulik, Thomas M.
Abstract : Objectives . To evaluate, in hilar cholangiocarcinoma (HCCA), the prognostic impact of specific preoperative radiologic parameters on resectability, metastases, and yield of laparoscopy, and to evaluate the currently used staging systems. Methods . Consecutive patients with HCCA presenting in our center from January 2003 through August 2010 were evaluated. Suspicion on lymph node metastasis, portal vein and hepatic artery involvement, lobar atrophy, and proximal extent of ductal invasion was scored. The prognostic value of these parameters for predicting resectability, yield of diagnostic laparoscopy, likelihood of metastatic disease, R0 resection, and survival was assessed. The Bismuth-Corlette classification and MSKCC staging system were evaluated. Results . Of all 289 evaluated patients, 158 patients (55%) had unresectable disease based on cross-sectional imaging studies or diagnostic laparoscopy; 131 patients (45%) underwent exploration. 83 patients (64%) underwent resection, of whom 67 (87%) had a radical (R0) resection. Suspicious lymph nodes and involvement of the hepatic artery were important prognostic factors for resectability. Predictive power of the evaluated staging systems was limited. Conclusions . Current staging systems predict resectability, but there is room for improvement. Hepatic artery involvement and nodal status might be important factors for prediction of resectability and should be considered in future staging systems.